2013
DOI: 10.1097/aln.0b013e31829419d3
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Cardiopulmonary Bypass and Erythrocyte Transfusion in the Pathogenesis of Pulmonary Dysfunction in Swine

Abstract: Background: Allogeneic erythrocyte transfusion in cardiac surgical patients is associated with a fourfold increase in pulmonary complications. Our understanding of the processes underlying these observations is poor and there is no experimental model of transfusion-related acute lung injury that shows homology to cardiac surgical patients. Our objective was to develop a novel swine recovery model to determine how two clinical risk factors, allogenic erythrocyte transfusion and cardiopulmonary bypass, interact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 34 publications
7
44
0
4
Order By: Relevance
“…Hence, the true risk of non‐antibody‐mediated TRALI may have been under‐appreciated. In contrast, data from various animal models have demonstrated a clear association between the transfusion of older PRBC and platelet products, with pulmonary dysfunction and the development of TRALI (Table ) .…”
Section: What Is Non‐antibody‐mediated Trali?mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the true risk of non‐antibody‐mediated TRALI may have been under‐appreciated. In contrast, data from various animal models have demonstrated a clear association between the transfusion of older PRBC and platelet products, with pulmonary dysfunction and the development of TRALI (Table ) .…”
Section: What Is Non‐antibody‐mediated Trali?mentioning
confidence: 99%
“…Microparticles (MPs) have also been identified as potential BRMs which accumulate in both platelet and PRBC units during routine storage . The effect of BRMs from stored blood products has been demonstrated through in vitro models as well as small and large animal models, which have been summarized in Table .…”
Section: What Is Non‐antibody‐mediated Trali?mentioning
confidence: 99%
“…Comparison of animals commonly used to model transfusion against humans. (Adapted from Simonova et al[19])[2,[13][14][15][16][18][19][20][21][22][23] …”
mentioning
confidence: 99%
“…33 Experimental studies have shown that these changes cause inflammatory organ injury through complex mechanisms including platelet and monocyte activation, endothelial injury and oxidative stress and the loss of microcirculatory autoregulation. [255][256][257][258] This results in paradoxical tissue hypoxia, despite apparently adequate oxygen delivery, tissue inflammation and organ dysfunction. The most important change that occurs in stored red cells over time is the depletion of high-energy phosphates.…”
Section: Introductionmentioning
confidence: 99%